A digital calibration technique for N-channel time-interleaved ADC based on simulated annealing algorithm. (March 2023) - Zhang, Yuhao; Han, Chenxi; Liu, Shubin
Abstract: This work proposes a digital calibration technique for time-interleaved analog-to-digital converters with any interleaving factor, which can calibrate gain, timing, and bandwidth mismatches. A simulated annealing algorithm is used to search the optimum calibration coefficients for the error correction module, possessing a customizable search range and precision. Furthermore, the calibration technique is effective for the single-tone, and multi-tone input signals in the whole Nyquist frequency. In the case of an 8-channel 12-bit TI-ADC with fixed mismatches, simulations show an SNDR improvement of 46.38 dB for a single-tone input and an SNDR improvement of 29.23 dB for a multi-tone input.